The state of soccer analytics - Pleuler, D.; Heaps, T.; Spearman, W.; Walder, S. (New England Symposium on Statistics in Sports, 2019)
"The State of Soccer Analytics" - panel discussion among Devin Pleuler, Tyler Heaps, and Will Spearman, with Seth Walder as moderator, at the 2017 New England Symposium on Statistics in Sports, held on Sept 28, 2019, at the Harvard University Science Center.